Association Between Leptin (-2548G/A) Genes Polymorphism and Breast Cancer Susceptibility: A Meta-Analysis. Issue 4 (January 2016) - Yan, Wanjun; Ma, Xingcong; Gao, Xiaoyan; Zhang, Shuqun
Abstract : Abstract: Leptin is a confirmed breast cancer susceptibility gene. However, published studies reported mixed results. This meta-analysis was conducted to systematically get a more accurate estimation of the association between the Leptin (-2548G/A) gene polymorphism and breast cancer risk. To assess the effect of Leptin (-2548G/A) gene polymorphism on breast cancer susceptibility, we searched PUBMED, ISI Web of Knowledge, EMBASE, Chinese National Knowledge Infrastructure (CNKI) databases until September 2015 to identify eligible studies, without restriction. Summary odds ratios (ORs) and 95% confidence intervals (CIs) were used to evaluate the susceptibility to breast cancer. Separate analyses were conducted on features of the population such as ethnicity, source of controls, and country. A total of 9 case-control studies on Leptin (-2548G/A) gene polymorphism and breast cancer risk, including 3725 cases and 3093 case-free controls were identified. The results revealed that compared with the G allele, the A allele was associated with modestly increased risk of overall breast cancer (A vs G: OR = 1.12, 95%CI = 1.04 − 1.20, P  = 0.002, P het P  < 0.00001). Following further stratified analyses, in the subgroup analyses by ethnicity, a significantly increased risk was observed among Caucasian (A vs G: OR = 1.11, 95%CI = 1.03–1.20, P  = 0.006, P het  = 0.00001). No publication bias was found in the present study. In conclusion, our meta-analysis suggests that the Leptin (-2548G/A) gene polymorphism plays an important role in breast cancer susceptibility, especially in Caucasian.